Global business networks and technology = Globalne sieci biznesowe a technologia - Pomykalski, Andrzej (Zielona Góra: Faculty of Economics and Management Press)
The current economic development changes the perception of technology innovation and business cooperation. Global business networks create very competitive markets characterised by constant innovation and dynamic changes. Further changes may come with growing involvement of active consumers and the development of Internet of Things.
Keywords: globalne sieci biznesowe; innowacje; współpraca przedsiębiorstw; badania; global business networks; innovation; researches